2020
DOI: 10.1038/s41419-020-2443-y
|View full text |Cite
|
Sign up to set email alerts
|

Combinatorial control of Spo11 alternative splicing by modulation of RNA polymerase II dynamics and splicing factor recruitment during meiosis

Abstract: Homologous recombination and chromosome segregation in meiosis rely on the timely expression of two splice variants of the endonuclease SPO11, named α and β, which respectively skip or include exon 2. However, in spite of its physiological importance, the mechanism underlying Spo11 alternative splicing in meiosis is still unknown. By screening the activity of factors that are predicted to bind the alternatively spliced region of Spo11, we identified hnRNPH as a key regulator of SPO11α splicing in mouse spermat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 36 publications
2
6
0
Order By: Relevance
“…As previously reported 33 , Spo11 showed a signi cantly changed alternative splicing (Spo11α/β) from P14 to P18, and the inclusion of its exon 2 is suppressed at the latter stage (Fig. 5i-j).…”
Section: Lack Of Hnrnph1 In Male Germ Cells Disrupts Meiotic Processessupporting
confidence: 84%
See 1 more Smart Citation
“…As previously reported 33 , Spo11 showed a signi cantly changed alternative splicing (Spo11α/β) from P14 to P18, and the inclusion of its exon 2 is suppressed at the latter stage (Fig. 5i-j).…”
Section: Lack Of Hnrnph1 In Male Germ Cells Disrupts Meiotic Processessupporting
confidence: 84%
“…Given that previous studies reported that unpaired sex chromosomes in male mice could be caused by abnormal Spo11 pre-mRNA splicing 32 and hnRNPH1 was identi ed as a key regulator of Spo11α splicing in mouse spermatocytes 33 , we next wanted to examine whether the Spo11 pre-mRNA splicing is changed in hnRNPH1 cKO spermatocytes. Although changed alternative splicing of Spo11 was not identi ed in our RNA-Seq data, considering the imperfect accuracy of RNA-seq, we decided to re-examine Spo11 splicing in P14 and P18 testes, isolated spermatocytes and spermatids from adult testis by RT-PCR, respectively.…”
Section: Lack Of Hnrnph1 In Male Germ Cells Disrupts Meiotic Processesmentioning
confidence: 99%
“…For example, ATP binding has been shown to be involved in the regulation of oocyte formation ( Quiroz et al, 2020 ). The RNA polymerase II involved in a combinatorial control of the timely regulated Spo11 splicing during the process of meiosis ( Cesari et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…It can be illustrated that ATP binding has been reported to participate in the oogenesis regulation ( 34 ). The RNA polymerase II was reported to be involved in the combinatorial control of Spo11 splicing, which is timely regulated during meiosis ( 35 ).…”
Section: Discussionmentioning
confidence: 99%